2019
DOI: 10.1634/theoncologist.2018-0876
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Clinical Trial Data Summation for BRAF-MEK Inhibition and Checkpoint Immunotherapy in Metastatic Melanoma

Abstract: Background Immune checkpoint inhibitors, along with BRAF and MEK inhibitors, have dramatically changed the management of and outlook for patients with metastatic melanoma. Analyses of long‐term follow‐up data and subanalyses based on disease characteristics may inform clinical decision making. Methods Reports of clinical trials in metastatic melanoma published between January 1, 2012, and August 30, 2018, were identified using PubMed (terms: melanoma AND [dabrafenib OR trametinib OR vemurafenib OR cobimetinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 82 publications
(127 reference statements)
0
15
0
2
Order By: Relevance
“…It has been reported that single-agent checkpoint inhibitors produced a clear clinical benefit over chemotherapy in metastatic melanoma, and these benefits appeared to be consistent across patient subgroups [66]. Moreover, combination of nivolumab plus ipilimumab, an anti-CTLA-4, was significantly more effective in term of objective response rate, progression-free survival and overall survival relative to ipilimumab used alone [66]. However, because checkpoint receptors play important roles in regulating autoimmunity, the major toxicities associated with the use of these drugs include autoimmune symptoms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been reported that single-agent checkpoint inhibitors produced a clear clinical benefit over chemotherapy in metastatic melanoma, and these benefits appeared to be consistent across patient subgroups [66]. Moreover, combination of nivolumab plus ipilimumab, an anti-CTLA-4, was significantly more effective in term of objective response rate, progression-free survival and overall survival relative to ipilimumab used alone [66]. However, because checkpoint receptors play important roles in regulating autoimmunity, the major toxicities associated with the use of these drugs include autoimmune symptoms.…”
Section: Discussionmentioning
confidence: 84%
“…This led to an interest in immunotherapeutic agents to extend the therapeutic effect and induce long-acting anti-melanoma effects, and immune checkpoint inhibitors are another important treatment option for patients with advanced melanoma [11,16,52]. It has been reported that single-agent checkpoint inhibitors produced a clear clinical benefit over chemotherapy in metastatic melanoma, and these benefits appeared to be consistent across patient subgroups [66]. Moreover, combination of nivolumab plus ipilimumab, an anti-CTLA-4, was significantly more effective in term of objective response rate, progression-free survival and overall survival relative to ipilimumab used alone [66].…”
Section: Discussionmentioning
confidence: 99%
“…Although the 5‐year OS is speculated to be in the range of 20% based on the Kaplan–Meier curves, it does not reach the satisfactory level. The 5‐year OS for advanced melanoma that has been reported in some global clinical trials has improved to as high as 50–60% 2 . However, due to some eligibility restrictions, some discordance may be expected with regard to the prognosis between clinical trials and real‐world clinical data, and so it may prove difficult to apply those clinical trial data to our practice in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…One of these two approaches is small-molecule inhibitors of the B-Raf proto-oncogene (BRAF) and the mitogen-activated protein kinase; the other involves immunotherapeutic antibodies directed at cytotoxic T-lymphocyte-associated protein 4 (CTLA) and programmed death 1 (PD-1). 2 These new agents have now been approved in several countries, including Japan. 3 Although prolonged long-term OS of patients with advanced melanoma has been shown in clinical trials, it is important for clinicians to know the "real-world" efficacy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly targeted therapies and immune checkpoint inhibitors have improved the prognosis of advanced melanoma. Although the objective response rates to those treatments range from 40-70% in clinical trials [1], real-world outcomes are inferior [2]. Therefore, prediction of drug response and optimization of treatment order are required.…”
Section: Introductionmentioning
confidence: 99%